Motisi Ubek Ritual in Traditional Medicine in Nagari Sumpur Kudus Selatan, Sumpur Kudus District, Sijunjung Regency - Ulfa Putrinilam Sari; Febri Yulika; Septriani, Septriani (Kirana Publisher (KNPub), 2024)
Research entitled Motisi Ubek Ritual in Traditional Medicine in Nagari Sumpur Kudus Selatan, Sumpur Kudus District, Sijunjung Regency. This research aims to find out the history and describe the procession of ritual implementation as well as the symbolic meaning contained in the motisi ubek ritual in treatment. The theory used is the ritual theory of Victor Turner and the symbolic interpretative theory of Clifford Geerzt. The method used is a qualitative method, with data collection techniques of observation, interviews and documentation. The results of this research show that the motisi ubek ritual is an expression of gratitude to Allah SWT, as a thank you to the shaman, to avoid conflict, and to provide new hope for the patient. The motisi ubek ritual has three stages, namely preparation, implementation and closing. The meaning of the motisi ubek ritual in general is to cleanse oneself of the remnants of disease if they are still left in the body and this is reflected in all the completeness of the ritual requirements.